Alternatively the Role of Parents - Smetanová, Dorota (Kultura-Społeczeństwo-Edukacja, 2012)
Topic of homosexuality is gradually coming to consciousness (not only) in Slovak society and it also due to the many professional works, which after the political changes in the last decade in our country gradually emerge from the depths of the taboo spheres to the spheres of ideological confrontations and constructive discussions. We do not claim that our society has reached the necessary level of debate both groups, heterosexual majority and gay and lesbian minority. However, took a path whose goal has signs of democratic society. All new phenomena must strike a long way till they are completely understated, accepted by society and at last integrated to the common life of society. Homosexuality is such a phenomenon. This path is a test of endurance gays and lesbians and heterosexuals test of democratic thinking. The contribution we tried to transmit a little further from the general question of homosexuality, specifically one of the areas described below, which is an area of „presence” of the child in the gay and lesbian partnerships.